1987
DOI: 10.1136/jmg.24.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Duplication 9p due to unequal sister chromatid exchange.

Abstract: A case of trisomy 9p syndrome is reported. The karyotype showed a tandem duplicatiQn of the short arm and of the inverted heterochromatic block of chromosome 9. Unequal sister chromatid exchange seems to be the only possible cause of this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…In such a case of de novo pure trisomy 9p, an intriguing mechanism has been proposed that the trisomy is due to a 3:1 segregation of a de novo given translocation involving chromosome 9p at gametogenesis [Mattina et al, 1986]. However, the microsatellite polymorphism study in the girl we described provided evidence for another mechanism resulting in the particular extra chromosome.…”
Section: Discussionmentioning
confidence: 74%
“…In such a case of de novo pure trisomy 9p, an intriguing mechanism has been proposed that the trisomy is due to a 3:1 segregation of a de novo given translocation involving chromosome 9p at gametogenesis [Mattina et al, 1986]. However, the microsatellite polymorphism study in the girl we described provided evidence for another mechanism resulting in the particular extra chromosome.…”
Section: Discussionmentioning
confidence: 74%
“…Several cases of tandem 9p duplications [Chiyo et al, 1976: case 8;Baccichetti et al, 1979: case 1;Fryns et al, 1979;Zadeh et al, 1981: case 1; Coco and Penchaszadeh, 1982: case 192;Cuoco et al, 1982: case 2; Motegi et al, 1985;Mattina et al, 1987;Haddad et al, 1996;Fujimoto et al, 1998;Guanciali et al, 2000;Kotzot et al, 2000: cases 11 and 12) or inverted 9p duplications [Teebi et al, 1993;Seghezzi et al, 1999] have been reported. The breakpoints range from the entire short arm to smaller 9p regions including either distal or interstitial segments.…”
Section: Discussion the Rearrangementmentioning
confidence: 96%
“…In only two of the previously reported cases, the origin could be clarified. In both cases, one of the parents was an inversion carrier (one paternal paracentric inversion [Phelan et al, 1993] and one maternal pericentric inversion [Mattina et al, 1987]), and unequal sister chromatid exchange was found to be the most likely mechanism of formation in both cases. In our two de novo cases, the origin of the duplication was maternal in the first case and paternal in the second.…”
Section: Discussionmentioning
confidence: 93%
“…Duplications may be formed by various mechanisms, like unequal meiotic crossing over, unequal exchange between homologous chromosomes before meiosis, or unequal sister chromatid exchange (Mattina et al, 1987). In only two of the previously reported cases, the origin could be clarified.…”
Section: Discussionmentioning
confidence: 96%